A 3D mathematical model of coupled stem cell-nutrient dynamics in myocardial regeneration therapy. (21st March 2022) - Andreucci, D.; Bersani, A.M.; Bersani, E.; Trujillo, F.J. León; Marconi, S.
Highlights: We recall some preliminaries concerning stem cell therapy for cardiac regeneration and related mathematical models. We write the systems of partial differential equations and the boundary and initial conditions. We show some numerical results obtained integrating numerically the systems of equations. Abstract: Stem cell therapy is a promising treatment for the regeneration of myocardial tissue injured by an ischemic event. Mathematical modeling of myocardial regeneration via stem cell therapy is a challenging task, since the mechanisms underlying the processes involved in the treatment are not yet fully understood. Many aspects must be accounted for, such as the spread of stem cells and nutrients, chemoattraction, cell proliferation, stages of cell maturation, differentiation, angiogenesis, stochastic effects, just to name a few. In this paper we propose a 3D mathematical model with a free boundary that aims to provide a qualitative description of some main aspects of the stem cell regenerative therapy in a simplified scenario. The paper mainly focuses on the description of the shrinking of the necrotic core during treatment. The stem cell and nutrients dynamics are described through coupled reaction-diffusion problems. Proliferation, chemoattraction, tissue regeneration and nutrient consumption are included in the model.